BCM542: Research Methodology And Methods / Faculty of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2023)
The course provides the student with basic competencies to plan, conduct and analyse a research undertaking on a topic relevant to the construction industry. The competencies include what issues to consdier when choosing research subjects, identifying research problems, how to use library resources to unearth the relevant literature, how to construct questionnaires and conduct surveys, how to select research design and use statistical and non-statistical data analysis techniques, discuss the findings, and provide a written report of the research conducted. This will help students to improve in terms of conceptual, analytical, decision making, problem solving, and communication skills. Students are evaluated based on individual and group research proposals, and quizes